Islamic Expansion in the Ideology of Pancasila and State Sovereignty - Pohan, Ibnu Asqori; Vinata, Ria Tri (Political Science Program, Universitas Negeri Semarang, 2019)
Islam is a religion that is adopted by the majority of Indonesian people and is believed to be a guide to life in order to obtain salvation in the world and in life after death. It makes a significant contribution to the initial process of negotiations to formulate the nation's philosophy of life, namely Pancasila. As a life guideline, the Pancasila nation and state are the main reference to conceptualize the sovereignty meaning which is then derived into International Law owned by Indonesia. This article uses the approach of discourse analysis in the implementation of Islamic values in the ideology of Pancasila. Islam's most important contribution to Pancasila is the 'monotheism' element which is the essence of Islamic teachings. Therefore, the dichotomy of Islam and Pancasila, or Islam and Negara Kesatuan Republik Indonesia (NKRI) becomes no longer relevant.